(untitled) (Research, Society and Development, 2021)
Introduction: Autism spectrum disorder (ASD) is considered a global development disorder affecting language, cognition and social interaction. The immaturity, especially perceived by their families, exacerbates the difficulty to handle issues about sexuality, causing difficulty in accepting that the autistic has rights in relation to his/her sexual desires and manifestations. Objective: to analyze the scientific evidence concerning the sexual development in autistic teenagers. Methodological Approach: an integrative literature review was conducted by searching and synthesizing the findings of published studies regarding sexuality and autism. In a search conducted in the Virtual Health Library (VHL) database, it was used the following search strategy: Sexual Education, Sexuality, Adolescent and Autistic Disorder, as indexed in the Descriptors in Health Sciences (DeCS) and in the medical methods system of the English language Medical Subject Headings (MeSH). Furthermore, for the advanced search, the Boolean terminology "and" was applied. Hence, covering the period from 2015 to June 2020, in Portuguese, English and Spanish. Results: 05 articles have met the eligibility criteria, being selected and analyzed. The results indicate that the theme should be discussed considering the effective possibility of manifestation and experience of sexuality by those affected by ASD, thereby contributing to the improvement of their quality of life. Conclusion: although complex, it is fundamental to discuss the sexuality of people with some disabilities, limitations or other special needs, in order to question misconceptions, myths and exclusions.